Incidence of delirium after non-cardiac surgery in the Chinese elderly population: a systematic review and meta-analysis - Gong, Xiao-Yan; Hou, Dong-Jiang; Yang, Jing; He, Jia-li; Cai, Ming-Jin; Wang, Wei; Lu, Xian-Ying; Gao, Jing (Frontiers in Aging Neuroscience, 2023)
Background: As the ageing situation becomes more acute, the number of elderly people undergoing surgery is increasing every year, POD places a heavy burden on the healthcare system. As a large country with a serious ageing population, China's elderly population has reached 267 million. To date, there has been no summary analysis of the pooled incidence of POD in the Chinese elderly population. Methods: Systematic search databases included PubMed, Web of Science, EMBASE, Cochrane Library Databases, China Knowledge Resource Integrated Database(CNKI), Chinese Biomedical Database(CBM), WanFang Database, Chinese Science and Technology Periodicals(VIP). The retrieval time was from the establishment of the database to February 8, 2023. The pooled incidence of delirium after non-cardiac surgery was calculated using a random effects model. Meta-regression analysis, subgroup analysis and sensitivity analysis were used to explore the source of heterogeneity. Results: A total of 52 studies met the inclusion criteria, involving 18,410 participants. The pooled incidence of delirium after non-cardiac surgery in the Chinese elderly population was 18.6% (95% CI: 16.4-20.8%). Meta-regression results showing year of publication as a source of heterogeneity. In the subgroup analysis of the incidence of postoperative delirium, gender subgroup shows 19.6%(95%CI=16.9%-22.3%) in male and 18.3%(95%CI=15.7% -20.9%) in female, year of publication subgroup shows 20.3% (95%CI=17.4%-23.3%) after 2018 and 14.6% (95%CI=11.6%-17. 6%) in 2018 and before, surgical types shows that hip fracture surgery 20% (95%CI=17.6%- 24.3%), non-cardiac surgery18.4%(95%CI=11.8%- 25.1%), orthopaedics surgery16.6%(95%CI=11.8%-21.5%), abdominal neoplasms surgery14.3%(95%CI=7.6%-21.1%), abdominal surgery13.9% (95%CI=6.4% -21.4%), measurement tool subgroup shows 19.3%(95%CI= 16.7%-21.9%) with CAM and 16.8%(95%CI=12.6%-21.0%) with DSM, sample size subgroup shows 19.4%(95%CI=16.8%-22.1%) for patients ≤500 and 15.3%(95%CI=11.0%-19.7%) for patients >500. Sensitivity analysis suggesting that the pooled incidence of postoperative delirium of this study were stable. Conclusion: Our study systematically reviewed the incidence of delirium after non-cardiac surgery in the elderly in China and showed a high incidence of postoperative delirium. Based on the current state of research, the incidence of postoperative delirium is higher for hip fracture surgery among the various types of surgery, with the exception of cardiac surgery, but needs to be further explored in future large sample studies.